Family Engagement in Qur’anic Learning: Improving Students’ Reading Skills Through the Ummi Methode - Raikhan; Muhammad Fajrun Nada (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2025)
One of the innovations that has developed is the textbook for learning how to read the Qur'an, the Ummi method, which is widely implemented in Qur'anic education. However, family engagement in supporting Qur’anic learning remains underexplored, despite its significant role in children’s achievement. This study aims to examine the forms of family involvement, supporting strategies, students’ reading achievements, and the enabling and inhibiting factors in the application of the Ummi Method. Using a qualitative case study design at TPQ Tanwirul Ma’arif, Lamongan, data were collected through interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings indicate that families actively contribute through daily mentoring, spiritual motivation, provision of learning facilities, participation in parent forums, and parent training. Strategies include collaboration with teachers, role modeling, reward and punishment systems, and strengthening religious values. As a result, more than 95% of students achieved fluency, tajwid accuracy, and reading confidence. The study contributes to the theoretical development of family engagement in Islamic education by institutionalizing parental roles through parent forums and training programs and offers a practical model of family-institution partnership replicable in other institutions